Evidence of Severe Acute Respiratory Syndrome Coronavirus 2 Replication and Tropism in the Lungs, Airways, and Vascular Endothelium of Patients With Fatal Coronavirus Disease 2019: An Autopsy Case Series. (27th January 2021) - Bhatnagar, Julu; Gary, Joy; Reagan-Steiner, Sarah; Estetter, Lindsey B; Tong, Suxiang; Tao, Ying; Denison, Amy M; Lee, Elizabeth; DeLeon-Carnes, Marlene; Li, Yan; Uehara, Anna; Paden, Clinton R; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic continues to produce substantial morbidity and mortality. To understand the reasons for the wide-spectrum complications and severe outcomes of COVID-19, we aimed to identify cellular targets of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) tropism and replication in various tissues. Methods: We evaluated RNA extracted from formalin-fixed, paraffin-embedded autopsy tissues from 64 case patients (age range, 1 month to 84 years; 21 COVID-19 confirmed, 43 suspected COVID-19) by SARS-CoV-2 reverse-transcription polymerase chain reaction (RT-PCR). For cellular localization of SARS-CoV-2 RNA and viral characterization, we performed in situ hybridization (ISH), subgenomic RNA RT-PCR, and whole-genome sequencing. Results: SARS-CoV-2 was identified by RT-PCR in 32 case patients (21 COVID-19 confirmed, 11 suspected). ISH was positive in 20 and subgenomic RNA RT-PCR was positive in 17 of 32 RT-PCR–positive case patients. SARS-CoV-2 RNA was localized by ISH in hyaline membranes, pneumocytes, and macrophages of lungs; epithelial cells of airways; and endothelial cells and vessel walls of brain stem, leptomeninges, lung, heart, liver, kidney, and pancreas. The D614G variant was detected in 9 RT-PCR–positive case patients. Conclusions: We identified cellular targets of SARS-CoV-2 tropism and replication in the lungs and airways and demonstrated its direct infection in vascular endothelium. This work provides important insights into COVID-19 pathogenesis and mechanisms of severe outcomes. Abstract : By analyzing tissues from patients with fatal COVID-19, using in situ hybridization and RT-PCR, we identified cellular targets of SARS-CoV-2 tropism and replication in the lungs, airways, and vascular endothelium. These findings provide important insights into COVID-19 pathogenesis and severe outcomes.